2020
DOI: 10.3390/ijerph17030853
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Single-Objective Optimization Protocols for Calibrating the Birds Nest Aquifer Model—A Problem Having Multiple Local Optima

Abstract: To best represent reality, simulation models of environmental and health-related systems might be very nonlinear. Model calibration ideally identifies globally optimal sets of parameters to use for subsequent prediction. For a nonlinear system having multiple local optima, calibration can be tedious. For such a system, we contrast calibration results from PEST, a commonly used automated parameter estimation program versus several meta-heuristic global optimizers available as external packages for the Python co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…This value of NSE lies in the range of "very good" according to the criteria adopted by Rauf and Ghumman [54]. Furthermore, our results are similar to those of Mohanty et al [55] and Lyons et al [16], although the hydraulic conductivity and specific storage were the most sensitive parameters in the calibration phase of their groundwater hydraulic model, but adjustment of the boundary condition was most crucial issue in our case. The resultant predicted vs. observed line was close to the 45-degree line, which also showed that the results of calibration were "very good".…”
Section: Hydraulic Model Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This value of NSE lies in the range of "very good" according to the criteria adopted by Rauf and Ghumman [54]. Furthermore, our results are similar to those of Mohanty et al [55] and Lyons et al [16], although the hydraulic conductivity and specific storage were the most sensitive parameters in the calibration phase of their groundwater hydraulic model, but adjustment of the boundary condition was most crucial issue in our case. The resultant predicted vs. observed line was close to the 45-degree line, which also showed that the results of calibration were "very good".…”
Section: Hydraulic Model Resultssupporting
confidence: 89%
“…Similar results were observed by previous studies [30,41,42,49]. This is most probably because a stronger optimization scheme was used in the scaled conjugate gradient to get a better global minimum with the minimum possible number of trials [16,54]. Further, the performance of the Scaled Conjugate Gradient training function was better than that of the Levenberg-Marquardt and Bayesian Regularization training functions for the three-layer architecture with 10 neurons (Figure 11a-d).…”
Section: Ann Model Resultssupporting
confidence: 88%